Effect of Inhaled Corticosteroids on Blood Glucose Homeostasis in Asthmatic Children - Alshaimaa Essam (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Asthma is a common disease especially in kids. The development of asthma symptoms appears to involve a combination of genetic predisposition and environmental factors. There are many medicines for asthma management, the most important of which is corticosteroid. High doses of inhaled corticosteroids can be associated with hyperglycemia risk increase.  Aim of the work: To detect the effect of inhaled corticosteroids on blood glucose homeostasis in asthmatic children. Patients and Methods:This study was conducted at pediatric inpatient and outpatient clinic of New Damietta Al-Azhar University Hospital in the period from September 2018 to September 2019, included 90 asthmatic children chosen randomly, 55 of them were males and 35 of them were females, aged from 2 to 12 years, For each child, the demographic data were collected, divided into three groups according to type of treatment, group I [using ICS only for more than 3 months], group  II [using SCS] and group III [using ICS & SCS]. Results: Regarding WBCs and its differentiation there was a significant increase in WBCs [7.8±2.1] and eosinophil [2.7±0.83]  in [group III] more than [group I]; WBCs [5.8±2.2]  and eosinophil [1.4±0.6] and [group II]; WBCs [6.4±2.0] and eosinophil [1.5±0.7].  Regarding blood glucose, [group I] mean value was [89.6±22.8]; [group II] was [91.6±17.3]; [group III] was [104.4±36.1]. There was statistically significant difference between group I with III and group II with III [P2: 0.032 and P3: 0.043]. Conclusion: Blood glucose level increased in children using both inhaled and systemic corticosteroids and it was significant statistically.